1984
DOI: 10.3758/bf03333769
|View full text |Cite
|
Sign up to set email alerts
|

Uniqueness of the self-concept across the life span

Abstract: College students and elderly subjects made self-descriptiveness and other-descriptiveness ratings for the same set of 120 trait adjectives representing three levels of likability. Elderly subjects attributed a greater number of likable traits uniquely to their best friend than to themselves alone, whereas young adults judged themselves more favorably than the other person. The elderly were generally slower at making the descriptiveness decisions, but particularly for uniquely descriptive items, as though trait… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

1984
1984
2012
2012

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 11 publications
(12 reference statements)
1
6
0
Order By: Relevance
“…However, there was no evidence to indicate that self-referencing eliminated the memory deficit of elderly adults relative to young adults. Because this outcome corroborates previous findings (e.g., Mueller & Ross, 1984), it seems unlikely that age differences in spontaneous self-referencing explain much of the retention deficit.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…However, there was no evidence to indicate that self-referencing eliminated the memory deficit of elderly adults relative to young adults. Because this outcome corroborates previous findings (e.g., Mueller & Ross, 1984), it seems unlikely that age differences in spontaneous self-referencing explain much of the retention deficit.…”
Section: Discussionsupporting
confidence: 90%
“…Some studies have indicated that self-awareness differences are directly related to the benefits of self-referencing material. One previous study (Mueller & Ross, 1984) found that certain aspects of self-awareness, as measured by this instrument, are lower in elderly subjects. This pattern was also apparent here (see Table 1), with the elderly showing significantly lower scores on the private self-consciousness scale, t (38) = 2.92, p < .01 , and nonsignificantly lower scores on public self-consciousness, t (38) = 1.98, p < .06 , and social anxiety, t (38) = 1.45, p < .16 .…”
Section: Methodsmentioning
confidence: 71%
See 2 more Smart Citations
“…As to the reliability of the difference in reaction time for Self-Qnly and Both items, it appears that the slower speed of access for unique traits is reproducible. Mueller and Ross (1984), using the same adjectives, procedures, and target other (best friend) as were used here , observed that elderly subjects took longer for SelfOnly items than for Both items. It also seems this result holds for several variations in procedures.…”
Section: Discussionmentioning
confidence: 99%